REDUCTION-BY-PERCENTAGE COMPRESSION TECHNIQUE FOR REDUCING SIZES OF PLAINTEXT PRIOR TO ENCRYPTION ALGORITHM - Arif Mandangan,; Che Haziqah Che Hussin,; Darmesah Gabda,; Suriana Lasairaya, (Journal of Islamic, Social, Economics and Development, 2022)
Other than security, another major concern in cryptography is efficiency to ensurecryptosystem could be embedded and deployed in various communication devices. Encryptinghigh numbers of data would consume high computational and storage capacity costs. Theseissues could affect the efficiency of cryptosystem. One of the approaches to overcome theseissues is by integrating data compression technique into cryptosystem. To avoid any encryptionand decryption error, lossless compression techniques are deployed in cryptography. Thecompression techniques are deployed to reduce either the size or number of plaintexts prior toencryption algorithm. Nevertheless, the sizes of the compressed plaintext are still large. To dealwith this issue, we proposed a simple technique with ability for reducing the sizes of thecompressed plaintext. The inverse of this technique is able to recover the original value of thedata without any loss or difference compared to the original data. With smaller sizes, theencryption algorithm would process inputs with smaller sizes, and these could potentially makethe encryption algorithm be executed in cheaper computational and storage capacity costs.